Do Wages Really Compensate for Risk Aversion and Skewness Affection? - Joop Hartog; Wim P. M. Vijverberg (Institute for the Study of Labor (IZA), 2002)
Utility theory suggests that foreseeable risk should increase the compensation for work. This paper expands on this notion: on basis of utility theory, people should care not only about risk but also about the skewness in the distribution of the compensation paid. In particular, because the degree of risk aversion ought to decrease with income, people should appreciate a small chance of a substantial gain; they should exhibit an ?affection? for skewness. To test these hypotheses, this paper carefully develops various measures of risk and skewness by occupational/educational classification of the worker and finds supportive evidence: wages rise with occupational earnings variance and decrease with skewness. In order to identify the discount rate and the degree of risk aversion, we also apply structural modelling of education and occupational choice and allow for non-lognormal wage distributions.
Keywords: J3; D8; 330; Wage variability; wage risk compensation; Einkommen; Nutzentheorie; Risikoaversion; Lohn; Verdienstausfall; Risikoprämie; Schätzung; Theorie; Vereinigte Staaten; Einkommensunsicherheit